Trends in Regional Supply of Peritoneal Dialysis in an Era of Health Reform, 2006 to 2013. (June 2021) - Sloan, Caroline E.; Coffman, Cynthia J.; Sanders, Linda L.; Maciejewski, Matthew L.; Lee, Shoou-Yih D.; Hirth, Richard A.; Wang, Virginia
Peritoneal dialysis (PD), a home-based treatment for kidney failure, is associated with similar mortality, higher quality of life, and lower costs compared with hemodialysis. Yet <10% of patients receive PD. Access to this alternative treatment, vis-à-vis providers' supply of PD services, may be an important factor but has been sparsely studied in the current era of national payment reform for dialysis care. We describe temporal and regional variation in PD supply among Medicare-certified dialysis facilities from 2006 to 2013. The average proportion of facilities offering PD per hospital referral region increased from 40% (2006) to 43% (2013). PD supply was highest in hospital referral regions with higher percentage of facilities in urban areas ( p = .004), prevalence of PD use ( p < .0001), percentage of White end-stage renal disease patients ( p = .02), and per capita income ( p = .02). Disparities in PD access persist in rural, non-White, and low-income regions. Policy efforts to further increase regional PD supply should focus on these underserved communities.